Path Analysis for Maize (Zea mays) Silage Cerrado-Amazon Ecotone - Silva, Zildiney Dantas da; Santos, Weder Ferreira dos; Junior, Osvaldo José Ferreira; Maciel, Lucas Carneiro; Santos, Layanni Ferreira Sodré; Ribeiro, Antonio Henrique Camilo; Dias, Vanderlan Carneiro; Barbosa, Adriano Silveira; Fidelis, Cícero Antonio Sobreira; Lourenço Borges, Thaís Alves da Silveira; Peluzio, Joênes Mucci (International Journal of Advanced Engineering Research and Science, 2021)
The management of nitrogen fertilization is of paramount importance for the increase of corn silage productivity, by directly participating in the processes of cell division and expansion.It is extremely important to identify the characteristics that are associated with the responsiveness of the use of nitrogen fertilization.Therefore, this study aims to identify the characteristics that most influence the total weight in maize silage production.Two trials were conducted, one with low nitrogen dosage (0 kg ha-1 of N in cover) and the other with a high dosage (120 kg ha-1 of N in cover), performed in the harvest 2017/18, in Sítio Vitória, in the municipalityof Santa Maria das Barreiras, State of Pará, located in the ecotone Cerrado-Amazon. The experimental design used was randomized blocks with eleven treatments and three replications.The treatments used were BRS 3046, M274, AG 8088, ANHEMBI, PR 27D28, P33-16, P32-11, P29-M12, P36-19, P40-8, and AG 1051. The base fertilization was performed in the groove manually supplying the needs of chemical and physical analysis. Whole plants of the useful plot were harvested and the characteristics were measured forplant height, insertion height of the first ear, culm diameter, the diameter of the ear, weight of the stem leaf, ear weight, and total plant weight. Track and variance analyses were performed through the Genes computer program. Variance analysis was performed for Low and High N, and track analyses for low N, high N, and average values conditions.